Faktor perubahan amalan adat tradisi dalam proses penanaman padi sawah tradisional masyarakat Dusun Kuruyou di Kg. Liau Darat, Bingkor, Sabah - Constant Vianney Cyril Chin (Penerbit UMS, 2020)
The Dusun Kuruyou community in Kampung Liau Darat, like any other community, have their own and unique traditional customs and beliefs. Other than having high values in society, the traditional customs of the Kuruyou community also serve as a symbol of the identity of their community. However, their traditional customs also do not escape the threat of change either due to internal factors or external factors that occur in their lives. These factors not only affect the life of the Dusun Kuruyou community in Kampung Liau Darat but also have changed some traditional customs practices in the process of rice cultivation which is common and often practiced in the life of their community, especially in the context of traditional rice cultivation. This study is a qualitative study that aims to identify the factors that have caused changes in traditional customs practices in the process of rice cultivation of the Dusun Kuruyou community in Kg. Liau Darat. This study area (Kg. Liau Darat) is located in Keningau district and is one of the villages that became the original settlement area of the Dusun Kuruyou community (Spitzak, 1997) after they migrated from the Nunuk Ragang area. The analysis of this study was done based on primary data and secondary data. Primary data were obtained from interviews and field observations conducted in the field. The analysis of this study shows that the main factor in the occurrence of changes in customary practices in the process of rice cultivation of the Dusun Kuruyou community is because the practice is contrary to the principles of religious teachings that they follow today (Christian). As a result, the traditional customary practices practiced today are no longer the same as those once practiced in the past. Thus, this study is important because it can see how the factors of change play a role in influencing the changes that occur in the traditional customary practice of rice cultivation of Dusun Kuruyou community and at the same time also examines the implications of changes in the traditional practice of traditional rice cultivation on the life of the Dusun Kuruyou community.